STEM Approach: The Development of Optical Instruments Module to Foster Scientific Literacy Skill - Noly Shofiyah; Metatia Intan Mauliana; Istiqomah Istiqomah; Ria Wulandari (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2021)
The STEM is an approach that seemly considered will be useful in online learning, because it can facilitate students to learn some skills from about 21st century. This study was aimed to develop module-based STEM in improving scientific literacy skills in distance learning through e learning. Because this research developed module-based STEM, this study was named developmental research. The research procedure follows the stages of the R & D method developed by Barg and Gall which includes the studies of preliminary, product planning, development, validation (validation by experts), and revision, lastly field testing. Moduls that have been declared valid by experts are field tested using one group pretest-posttest design in an experimental class. The results show that the feasibility of module-based STEM in distance learning model to increase students' skills within scientific literacy was valid with the average score of 4.28 by two experts. In addition, the application of integrated STEM teaching materials through e-learning has a moderate effect on students' scientific literacy skills since the N-gain score was 0.6.